2021
DOI: 10.1002/wcms.1578
|View full text |Cite
|
Sign up to set email alerts
|

How to strike a conformational balance in protein force fields for molecular dynamics simulations?

Abstract: Molecular dynamics (MD) simulation is a powerful tool for exploring the conformational energy landscape of proteins, and the reliability of MD results is crucially dependent on the underlying force field (FF). An accurate FF capable of producing balanced distributions of diverse conformations at multiple levels has been a long‐sought goal. Towards this, several decades of joint efforts have been made to address FF deficiencies, manifested by conformational biases at different levels (local conformations, secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 288 publications
(872 reference statements)
0
14
0
Order By: Relevance
“…In a significant development, residue-specific force fields have been introduced. [41] These force fields use in addition coil library information from the Protein Data Bank (PDB) by incorporating the individual backbone φ,ψ propensities of each residue type. [41][42][43][44][45][46][47] Such residuespecific force fields, in combination with suitable water models, can provide an improved representation of disordered states while retaining the properties of ordered proteins.…”
Section: Introductionmentioning
confidence: 99%
“…In a significant development, residue-specific force fields have been introduced. [41] These force fields use in addition coil library information from the Protein Data Bank (PDB) by incorporating the individual backbone φ,ψ propensities of each residue type. [41][42][43][44][45][46][47] Such residuespecific force fields, in combination with suitable water models, can provide an improved representation of disordered states while retaining the properties of ordered proteins.…”
Section: Introductionmentioning
confidence: 99%
“…ff14IDPSFF does not exhibit any helix formation in their conformations and instead adopts b-strands, even b-hairpins, which are formed within the NAC domain itself or together with the amino acids of the N-terminal domain. The cluster 1 centroid has b-strands (residues 1-4, 14-20, 40-42, and 58-61) formed between the NAC and N-terminal domains, and a short b-hairpin (residues [29][30][31][32][33][34][35] in the NAC domain itself. The centroids of clusters 2 and 3 present larger b-hairpins that involved different amino acids of the NAC domain.…”
Section: Conformational Samplingmentioning
confidence: 99%
“…In fact, previous studies on differences between the standard and modern force fields have demonstrated high sensitivity in obtaining IDP conformational ensembles. 28,29 Approaches to include intrinsic disorder can range from adjusting the dihedral parameters (CHARMM22*, 30 RSFF2 31 and OPLS-AA/M 32 force fields), adding a grid-based energy correction term to the ϕ / ψ dihedral energy surface called the CMAP method (CHARMM36, 33 ff14IDPSFF, 34 and ESFF1 35 ) and refining the protein–water interactions (a99SB-disp, 36 ff03ws, 37 and CHARMM36m 38 ). Among these new force fields, ff14IDPSFF has been developed as a promising force field capable of correcting the dihedral distributions of all 20 amino acids from the popular ff14SB 39 force field but assisted using the CMAP method.…”
Section: Introductionmentioning
confidence: 99%
“…(41) These force fields use in addition coil library information from the Protein Data Bank (PDB) by incorporating the individual backbone j,y propensities of each residue type. (41)(42)(43)(44)(45)(46)(47) Such residue-specific force fields, in combination with suitable water models, can provide an improved representation of disordered states while retaining the properties of ordered proteins.…”
Section: Introductionmentioning
confidence: 99%
“…(41) These force fields use in addition coil library information from the Protein Data Bank (PDB) by incorporating the individual backbone φ,ψ propensities of each residue type. (4147) Such residue-specific force fields, in combination with suitable water models, can provide an improved representation of disordered states while retaining the properties of ordered proteins. With respect to water models, TIP4P-D and closely related derivatives have been notably successful in preventing overly compact conformations by favoring more extended IDP structures showing improved agreement with experiment.…”
Section: Introductionmentioning
confidence: 99%